Pure beauty : judging race in Japanese American beauty pageants - King-O'Riain, Rebecca Chiyoko (University of Minnesota Press, 2006)
Rebecca Chiyoko King-O'Riain studies Japanese American community beauty pageants in San Francisco, Los Angeles, Seattle, and Honolulu to discover how these pageants seek to maintain racial and ethnic purity amid shifting notions of cultural identity. Pure Beauty shows how racial and gendered meanings are enacted through the pageants, and reveals their impact on Japanese American men, women, and children.